Changes in the mechanical, structural and electrical properties of glassy carbon due to strontium and silver co-implantation and annealing - Odutemowo, O. S.; Malherbe, J. B.; Limbach, Rene; Wondraczek, Lothar; Wendler, E.; Undisz, A.; Njoroge, E. G.; Idisi, D. O.; Dhlamini, M. S. (Applied Surface Science, 2021)
The effect of Sr and Ag co-implantation and recovery annealing on the structural, mechanical and electrical properties of glassy carbon is reported. Glassy carbon was co-implanted with 200 keV Sr and Ag ions to a fluence of 1 × 1016 ions/cm2 at room temperature. Combination of Raman spectroscopy and high resolution transmission electron microscopy (HRTEM) showed that the co-implantation of Sr and Ag resulted in amorphisation of the glassy carbon substrate. Raman spectra and HRTEM micrographs obtained after annealing indicated recovery of the glassy carbon structure, however, the recovered structure appears to be graphite-like. Instrumented indentation experiments on the ion-irradiated glassy carbon substrates revealed the formation of a surface layer with considerably enhanced mechanical performance. When annealing the ion implanted samples, these effects were only partially reversible. The effect of the irradiation-induced amorphisation and graphitisation of glassy carbon on its conductivity was also studied. The sample became less conductive after Sr and Ag co-implantation, whereby annealing resulted in an increase in conductivity.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Electrical characterization; Glassy carbon; Heat treatment; HRTEM; Ion-implantation; Nano-hardness; Raman spectroscopy